Ontology-Based Risk Knowledge Construction for Integrated Pipeline Corridors - Bao-Jiang Han (Discrete Dynamics in Nature and Society)
In the construction process of different integrated pipe corridors, there exist a large number of similar and reusable risk analysis results. In order to improve the efficiency of risk analysis and the efficiency of dealing with accidents in the process of construction management of integrated pipeline corridors and systematize the fragmented risk analysis knowledge, this paper will build ontology-based knowledge for risk response in integrated pipeline corridors. This ontology knowledge base can not only standardize and informatize knowledge through the definition of knowledge attributes and classification of knowledge, which can help reuse risk management metaknowledge at different levels and greatly improve the efficiency of risk management, but also reason out the risk-causing mechanism and response strategy of new integrated pipeline corridor risk through the similarity between risks and the correlation between risk-causing factors, so as to realize the repeated application of risk knowledge.